Analisa Risiko Kecelakaan Kerja Di Stasiun Boiler Pada PT XYZ Dengan Menggunakan Metode HIRARC - Mahyunis Mahyunis; Zulham Effendi; Fauzi Asrianto (CV. IRA PUBLISHING, 2023)
Occupational Safety is the protection of work security experienced by workers both physically and mentally in the work environment. The production process in the boiler division has a very large potential for danger, so it is very important to improve training in the field of work safety. Several things that have potential hazards include the use of incomplete PPE, safety equipment, operation and maintenance, and operator negligence. This study identified the hazards in each activity at PT XYZ. The research findings cover 9 work activities and 14 potential hazards. Scraping activity in the boiler kitchen has the highest work accident rate, which is 34.89% and the operation of the control panel does not cause accidents, with an accident percentage of 0%. The average level of low risk is 10 and medium is 3. However, the PT XYZ has not fully implemented the complete use of Personal Protective Equipment (PPE) at the Boiler Station.